O Ewangelii ukrytej. Jakuba Malika kerygmatyczna interpretacja twórczości pozytywistów - Kaczmarek, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Jakub Malik’s (1970-2017) analyses of positivist texts have a few characteristic features. At first Malik showed interest in fulfilling gaps in literary studies, throwing light on the issues that were insufficiently explored by other scholars. In recent years his studies focused on the references to the Bible and Christianity in Polish positivist works. Especially the years 2008-2017 saw a significant turn towards the kerygmatic analysis, which helps to underline the relationship between the lives of characters, in particular those from Bolesław Prus’ Lalka, and Christian anthropology.